Research Progress of Application and Corrosion Resistance of Medical Magnesium Alloy Materials - XU Dong-guang, MA Chun-hua, ZHAO Ya-zhong, ZHONG Zhi-guo, LEI Yu-yu, LI Xiao-zhe, YANG Hao (Cailiao Baohu)
Magnesium alloys have good mechanical properties and good biocompatibility with humans. Especially, magnesium alloys possess the characteristics of biodegradable in the human body, which endows them as a kind of very promising biodegradable biomedical metal materials. In this work, the advantages and problems of magnesium and magnesium alloys as biodegradable biomedical materials was summarized, as well as the research status of magnesium alloys for biomedical applications at home and abroad. In addition, the corrosion mechanism and types of magnesium and magnesium alloys and the current methods for improving the corrosion resistance of pure magnesium and magnesium alloys for biomedical applications were introduce. The corrosion resistance of biomedical magnesium alloys in vitro and in vivo was compared, and the future development prospects and research directions of biodegradable biomedical materials were predicted.